Fractured Seduction. - Damianovic, Maia (Tel Aviv : Artifact Gallery, 1993)
Marcaccio, Fabian ; Ellis, Stephen ; Reed, David ; Lundsager, Eva ; Kim, Byron ; Fitzgerald, Gail ; Dona, Lydia ; Zinsser, John
Fractured Seduction, Artifact Gallery, Tel Aviv, 1993
Engels & Hebreeuws
kunstcatalogus